2012
DOI: 10.1113/jphysiol.2012.230532
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term in vivo imaging of normal and pathological mouse spinal cord with subcellular resolution using implanted glass windows

Abstract: Key points• Chronic in vivo imaging of cellular interactions within the adult spinal cord with subcellular resolution is important for understanding cellular physiology and disease progression.• Previous approaches for chronic in vivo spinal cord microscopy have required surgery for each imaging session.• Here we describe a novel method for implanting glass windows over the exposed spinal cords of adult mice for repeated in vivo microscopy.• We show that the windows remain clear for many months after implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 33 publications
4
85
0
Order By: Relevance
“…This enables collecting data about cellular infiltration and status of the BSCB in asymptomatic animals and relating them to the exact timing of disease onset. Chronic implants have been described and would be the optimal strategy to put forward to remedy the situation, because they allow repetitive imaging of the same animal in a longitudinal fashion (52,53). However, in our hands they are not suitable in the study of autoimmune diseases because they require animals to be administered with immunosuppressant or anti-inflammatory drugs to limit fibrosis over the surface of the spinal cord, a critical step to achieve acceptable success rates and in-depth high-resolution imaging.…”
Section: Resultsmentioning
confidence: 99%
“…This enables collecting data about cellular infiltration and status of the BSCB in asymptomatic animals and relating them to the exact timing of disease onset. Chronic implants have been described and would be the optimal strategy to put forward to remedy the situation, because they allow repetitive imaging of the same animal in a longitudinal fashion (52,53). However, in our hands they are not suitable in the study of autoimmune diseases because they require animals to be administered with immunosuppressant or anti-inflammatory drugs to limit fibrosis over the surface of the spinal cord, a critical step to achieve acceptable success rates and in-depth high-resolution imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Over time, this growth resulted in the loss of image contrast and resolution. This growth has also been seen in alternative surgical preparations 31 . Anecdotally, we have observed that this growth can be minimized by carefully washing the dorsal SC surface to remove blood products, sealing the surface of the cut bone with cyanoacrylate, sealing edges of the chamber well with silicone elastomer, and minimizing the interstitial space between the dorsal SC and the cover glass.…”
Section: Discussionmentioning
confidence: 92%
“…Hence, results obtained for these cases could have been better if we had chosen to simulate fields with higher amplitudes. (Fenrich et al (2012(Fenrich et al ( , 2013). …”
Section: Numerical Resultsmentioning
confidence: 99%